Molecular characterization of immunogenic cell death indicates prognosis and tumor microenvironment infiltration in osteosarcoma - Liu, Zhongyue; Liu, Binfeng; Feng, Chengyao; Li, Chenbei; Wang, Hua; Zhang, Haixia; Liu, Ping; Li, Zhihong; He, Shasha; Tu, Chao (Frontiers in Immunology, 2022)
Osteosarcoma (OS) is a highly aggressive bone malignancy with a poor prognosis, mainly in children and adolescents. Immunogenic cell death (ICD) is classified as a type of programmed cell death associated with the tumor immune microenvironment, prognosis, and immunotherapy. However, the feature of the ICD molecular subtype and the related tumor microenvironment and immune cell infiltration has not been carefully investigated in OS. Herein, we identified two ICD-related subtypes and found significant heterogeneity in clinical prognosis, TME, and immune response signaling among distinct ICD subtypes. Subsequently, a novel ICD-related prognostic signature was developed to determine its predictive performance in OS. Also, a highly accurate nomogram was then constructed to improve the clinical applicability of the novel ICD-related signature. Furthermore, we observed a significant correlation between ICD risk score and TME, immunotherapy response, and chemotherapeutic drug sensitivity. Notably, the in vitro experiments further verified that GALNT14 is closely associated with poor prognosis and malignant progress of OS. Hence, we constructed a novel classification system of OS based on ICD-related genes, which could help to improve our understanding of ICD in OS and provides new insights for the prediction of prognosis and development of effective immunotherapy strategies.